I-SceI-mediated double-strand DNA breaks stimulate efficient gene targeting in the industrial fungus Trichoderma reesei - Ouedraogo, Jean Paul (Appl Microbiol Biotechnol, 2015)
Targeted integration of expression cassettes for enzyme production in industrial microorganisms is desirable especially when enzyme variants are screened for improved enzymatic properties. However, currently used methods for targeted integration are inefficient and result in low transformation frequencies. In this study, we expressed the Saccharomyces cerevisiae I-SceI meganuclease to generate double-strand breaks at a defined locus in the Trichoderma reesei genome. We showed that the double-strand DNA breaks mediated by I-SceI can be efficiently repaired when an exogenous DNA cassette flanked by regions homologous to the I-SceI landing locus was added during transformation. Transformation efficiencies increased approximately sixfold compared to control transformation. Analysis of the transformants obtained via I-SceI-mediated gene targeting showed that about two thirds of the transformants resulted from a homologous recombination event at the predetermined locus. Counter selection of the transformants for the loss of the pyrG marker upon integration of the DNA cassette showed that almost all of the clones contained the cassette at the predetermined locus. Analysis of independently obtained transformants using targeted integration of a glucoamylase expression cassette demonstrated that glucoamylase production among the transformants was high and showing limited variation. In conclusion, the gene targeting system developed in this study significantly increases transformation efficiency as well as homologous recombination efficiency and omits the use of Δku70 strains. It is also suitable for high-throughput screening of enzyme variants or gene libraries in T. reesei. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s00253-015-6829-1) contains supplementary material, which is available to authorized users.